HIGH-PERFORMANCE CONCRETE BASED MINERAL ADDITIVES - Kuldasheva A. X; Maxammatov M (European Journal of Life Safety and Stability (2660-9630), 2021)
Research is shown, a literature review of various bibliographic sources on the use of additives of wollastonite and metakaolin for high-performance-concretewas conducted. Influence of additives among themselves and their influence on the properties of high-performance-concrete is analyzed.